Correction of violations rheology of blood in ischemic heart disease - Uzokov, Jurabek Baxtiyorovich; Khusainova, Munira Alisherovna; Eshmamatova, Fayyoza Boymamatovna; Mamadiyorova, Mashxura Mashrabovna (Science and Education, 2023)
The therapeutic effect of ozone-oxygenated crystalloids as a compensation factor for hemorheological disorders in patients with coronary heart disease has been studied. 53 patients with coronary heart disease: angina pectoris II>III FC aged 40 to 79 years were monitored. All patients received traditional antianginal therapy. Patients of the main groups were treated with ozone therapy against the background of traditional therapy. Before and after treatment, the apparent viscosity of blood, yield strength, shear stress were determined. A decrease in the studied parameters was revealed in all the studied groups and the absence of dynamics in patients, who received traditional therapy. It is concluded that parenteral administration of ozone-oxygenated crystalloids in therapeutic dosage contributes to the improvement of rheological properties of blood.